Biogas Production and Determination of Methanogens from Digester - Treated Palm Oil Mill Effluent - Zakaria @ Mamat, Mohd Rafein (2008)
Due to increasing awareness of the risk of the environmental pollution and emission of green house gases (GHG) that caused global warming, a study of palm oil mill effluent (POME) treatment using biological processes in close digesters has been conducted. Potentially beneficial methane gas production from this treatment has driven the objectives of this study to explore the methanogens from POME sludge and their characteristic in order to improve the POME treatment efficiency. A pilot plant digester with 500 m3 volume was operated for one year and biogas and methane production profiles were monitored daily. Parameters used for monitoring were pH, temperature, volatile fatty acids, chemical oxygen demand, biogas and methane concentration during the treatment. Structure of the flocs formation and methanogenic bacteria isolated from this digester was also carried out in order to understand the microbiological characteristics of the bioprocess involved Specific methanogenic activity test (SMA) and microscopic observation were carried out to support the existence of the methanogens that were able to produce methane gas. During POME treatment process, the highest methane concentration obtained was 55 % (v/v) and chemical oxygen demand (COD) removal efficiency was up to 95%. Anticipated active biomasses retained in the digester were determined as total solids (TS) and volatile suspended solids (VSS) at 2.5% and 1.5%, respectively. SMA test for acetolastic methanogens was determined in the range of 0.05 - 1.3 g COD/ g VSS/d. Microscopic observation of the sludge and isolated colonies have shown that the digester systems were dominated by microorganism resemble to Methanosaeta sp. and fluorescence microscope has proved that this microorganism exhibited autofluorescence green color.